2021
DOI: 10.1037/pla0000151
|View full text |Cite
|
Sign up to set email alerts
|

Culturally responsive play therapy with military-connected children and families: Opportunities for rigorous research.

Abstract: Military-connected children represent intersectional identities and demonstrate unique vulnerabilities and strengths. Indeed, the wellbeing of military families is complex given stressors related to frequent separations and geographic relocations, coupled with the high-risk nature of careers in the armed forces. However, military families also demonstrate several strengths, such as resilience, that may be overlooked in the mental health interventions offered to the military community's youngest members. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…It may be that counselors need to develop clinical interventions attuned to spouses, rather than as adjacent to the evidence-based practices for service members. This assertation aligns with previous researchers who reported that more attention is needed to develop culturally and developmentally responsive services for military spouses (Burgin & Prosek, 2021;NASEM, 2019).…”
Section: Implications For Counselingsupporting
confidence: 88%
See 2 more Smart Citations
“…It may be that counselors need to develop clinical interventions attuned to spouses, rather than as adjacent to the evidence-based practices for service members. This assertation aligns with previous researchers who reported that more attention is needed to develop culturally and developmentally responsive services for military spouses (Burgin & Prosek, 2021;NASEM, 2019).…”
Section: Implications For Counselingsupporting
confidence: 88%
“…For example, Mooney (2019) purported that depression and anxiety among military spouses served as risk factors to their resilience. In military communities, resilience is a core element of military ethos and is considered a significant protective factor for both service members and their families (Burgin & Prosek, 2021).…”
Section: Mental Health Symptoms Among Military Spousesmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the impact therapeutic powers of play have on mitigating the negative consequences of early childhood trauma, replication studies could provide additional evidentiary support for social systems to fund and provide children access to play outlets to mitigate ACEs within more diverse and marginalized populations (e.g., Deaf, immigrant, impoverished, multiracial, refugee, and religious minority). Consistent with current play therapy literature, the authors recommend recruiting adults from diverse and marginalized populations to further examine the therapeutic powers of play through the lens of intersectionality, similar to what other play therapy researchers have done (e.g., Agarwal & Meany-Walen, 2019; Burgin & Prosek, 2021; Casey et al, 2021; Ceballos et al, 2020; Chase & Opiola, 2021; Killian et al, 2017; Kwon & Lee, 2018; Tapia-Fuselier & Ray, 2019). Specifically focusing on the therapeutic powers of play within these populations would increase play therapists’ understanding of the healing nature of multicultural play experiences.…”
Section: Discussionmentioning
confidence: 93%
“…The current special issue offers two more articles focused on play therapy with military families: “Culturally Responsive Play Therapy With Military-Connected Children and Families: Opportunities for Rigorous Research” (Burgin & Prosek, 2021) and “Serving Together: Play Therapy to Foster Attachment for Grieving Military Families” (Villarreal-Davis et al, 2021). These four manuscripts, over a 30-year period, demonstrate the need for more research and writing exploring play therapy applications with children of servicemembers and veterans as well as their families.…”
mentioning
confidence: 99%